RISK OF COMPLICATIONS FOR PREGNANT BACTERIAL VAGINOSIS - Rado, Ana (2015)
Objectives: To determine the risk of pregnancy complications by untreated bacterial vaginosis. Design: Retrospective study of historical cohort. Materials and Methods: Clinical histories were reviewed at the time of delivery for diagnosis of bacterial vaginosis in the first prenatal control. Results: One hundred thirty pregnant women with bacterial vaginosis did not complete their treatment and 447 pregnant women did not have bacterial vaginosis. There was no significant differences in maternal age, parity, history of vaginal discharge, presence of vaginal secretion, birth weight and route of delivery between the groups. Pregnant women with bacterial vaginosis had more risk of abortion (RR 4,185; p = 0, 01) and endometritis (RR 2,441; p = 0, 034). Risk for preterm delivery, chorioamnionitis, premature rupture of membranes and low birth weight was not significant. Conclusions: Bacterial vaginosis-induced risk for abortion and puerperal endometritis requires prompt diagnosis and treatment.